Microbiological Safety of Drinking Water in Dhaka City: A Study on Supply and Treated Water in Dhaka, Bangladesh - Shathi, Tahamina Akter; Roy, Partha Bikash; Supti, Mahima Hossain; Haque, Nabila; Das, Kamal Kanta (Stamford Journal of Microbiology, 2024)
Access to safe and clean drinking water is a fundamental human right and a critical public health issue worldwide. The present study attempted to determine the microbiological quality and detection of pathogenic bacteria in different municipal water supplied in the different places of Dhaka city. This study involved the microbiological analysis of sixteen drinking water samples collected from diverse sources, including four from supply points, six from consumer points, and six treated water samples, obtained from Siddeswari, Sonargaon, Mirpur, and Badda. All the samples were contaminated with different microorganisms, and the total viable bacterial count ranged from 103 to 10⁷ CFU/mL. Pathogenic microbes like Pseudomonas spp. was present in all the samples, while Klebsiella spp., Salmonella spp., and Staphylococcus spp. were predominantly present in seven, six, and eleven samples, respectively. We also aimed to determine whether Shigella spp. was present in all the samples, but it was completely absent. Escherichia coli was detected in samples from both supply and consumer points within the range of 102 to 103 cfu/mL. The results indicate that the treatment procedure is not sufficiently effective in eliminating all pathogenic bacteria, and unhygienic environments contribute to post-treatment contamination. The study revealed that government should take necessary action to ensure public health safety, particularly with regard to access to safe drinking water. Stam. J. Microbiol. 2024; 14(1):36-40